ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN PERMASALAHAN INTEGRAL TAK TENTU PADA MATA KULIAH KALKULUS INTEGRAL - Mimi Nur Hajizah (Jurnal Karya Pendidikan Matematika, 2019)
The purpose of this study is to identify, describe, and classify the types of student errors in solving indeterminate integral problems and find out the factors that cause these errors. This research is a type of descriptive research using qualitative research methods. The subjects in this study were students of the Mathematics Study Program FMIPA UNJ in 2018/2019 school year who were taking Integral Calculus courses. Data collection is done through tests and interviews. The test is conducted to obtain data on the types of errors made, while interviews are conducted to explore the causes of the mistakes made. The results of this study indicate the types of errors made by students based on the indicator approach are as follows. 1) Determine indeterminate integrals with the integration of substitution techniques. 2) Determine indefinite integrals with partial integration techniques. 3) Determine indeterminate integrals with the integration of trigonometric substitution techniques. 4) Determine indefinite integrals with the technique of rationalizing integrals. Factors causing errors include students lacking understanding of the concept of indeterminate integrals as anti-derivatives, difficulty in identifying the integrating techniques that must be applied, not proficient in carrying out integrating procedures, and errors in calculations.